Diffusivity of saturated ordinary Portland cement-based materials: A critical review of experimental and analytical modelling approaches. (December 2016) - Patel, Ravi A.; Phung, Quoc Tri; Seetharam, Suresh C.; Perko, Janez; Jacques, Diederik; Maes, Norbert; De Schutter, Geert; Ye, Guang; Van Breugel, Klaas
Abstract: This paper provides a comprehensive overview of existing experimental and modelling approaches to determine effective diffusion coefficients of water saturated ordinary Portland cement-based materials. A dataset for diffusivity obtained from different experimental techniques have been presented for cement paste, mortar and concrete. For cement paste at low porosities, diffusivity reported by different authors varies up to a factor of five and electrical resistivity measurements for low capillary porosity are up to one order of magnitude higher compared to other techniques. Experimental data of mortar and concrete reveals predominant influence of increasing tortuosity due to aggregates and limited influence of interface transition zone. Hence, a particular emphasis has been placed on assessing predictability of diffusivity models for cement paste on a larger dataset collected in this paper. It has been observed that all predictive models have similar level of accuracy and fail to predict electrical resistivity data at low capillary porosity as these models are not calibrated using electrical resistivity data.